Pembuatan Dan Uji Mutu Fisik Sediaan Toner Wajah Infusa Daun Belimbing Wuluh (Avverhoa Bilimbi L.): Pembuatan Dan Uji Mutu Fisik Sediaan Toner Wajah Infusa Daun Belimbing Wuluh (Avverhoa Bilimbi L.) - Burhamin, Yusriyani (Akademi Farmasi Yamasi Makassar, 2024)
Abstract. Facial toner research has been carried out using samples of starfruit leaves (Avverhoa Bilimbi L.) originating from Pinrang, South Sulawesi. The research was carried out with the aim of knowing the manufacture and quality testing of facial toner preparations from the infusion extract of starfruit leaves (Avverhoa bilimbi L). Simplisia starfruit leaves are extracted using the infusion method. This formula is made with a base (without extract) and concentrations of 10%, 20% and 30%. Physical quality tests carried out on facial toner preparations are organoleptic tests, pH tests, homogeneity tests and irritation tests. Organoleptic Results F0, F1, F2, F3 have liquid form, characteristic odor and are brown in color. The results of the pH test, homogeneity test and irritation test on the 10 panelists met the requirements because there was no irritation, itching or swelling on the skin.